Prognostic values of aquaporins mRNA expression in human ovarian cancer. Issue 2 (27th April 2018) - Chetry, Mandika; Li, Saisai; Liu, Hailing; Hu, Xiaoli; Zhu, Xueqiong
Abstract : Aquaporins (AQPs), a family of transmembrane channel, are composed of 13 identified members (AQP0–12). Accumulating evidences reported that AQPs were correlated with various biological roles and represented a prognostic predictor in various cancer types. However, the prognostic value of AQPs expression in ovarian cancer remains unclear. Using 'Kaplan–Meier plotter' (KM plotter) online database, we explored the predictive prognostic value of individual AQPs members' mRNA expression to overall survival (OS) in different clinical data, such as histology, pathological grades, clinical stages, TP53 status, and applied chemotherapy in ovarian cancer patients. Our results revealed that higher AQP0, AQP1, and AQP4 mRNA expression were correlated with poor OS, whereas higher AQP3, AQP5, AQP6, AQP8, AQP10, and AQP11 showed better OS in ovarian cancer patients. Moreover, AQP4 and AQP8 showed poor OS in TP53-mutated ovarian cancer patients and AQP1 presented unfavorable OS in both TP53 mutated and wild ovarian cancer patients. Additionally, AQP3, AQP6, and AQP11 mRNA expression were correlated with better OS, whereas AQP0 and AQP1 showed poor OS in all ovarian cancer patients treated with Platin, Taxol, and Taxol + Platin chemotherapy. AQP5, AQP8, and AQP10 were associated with improved OS, however, AQP4 predicted unfavorable OS in all patients treated with Platin chemotherapy. Our results suggest that individual AQPs, except AQP2 and AQP9, are associated with unique prognostic significance and may thus act as new predictive prognostic indicators and potential drug therapeutic target in ovarian cancer.